Efficacy and safety of ondansetron in preventing postanesthesia shivering: a meta-analysis of randomized controlled trials - Tie, Hong-Tao; Su, Guang-Zhu; He, Kun; Liang, Shao-Rong; Yuan, Hao-Wei; Mou, Jun-Huan (BMC anesthesiology, 2014)
Shivering is a very common complication in the postanesthesia period. Increasing studies have reported ondansetron may be effective in prevention of postanesthesia shivering (PAS). However, the results remained controversial; hence we conducted a meta-analysis of randomized controlled trials to evaluate the efficacy and safety of ondansetron on the prevention of postanesthesia shivering. PubMed and Embase databases were searched to identify the eligible randomized controlled trials assessing the effect of ondansetron on the prevention of PAS. Results were expressed as risk ratios (RRs) with accompanying 95% confidence intervals (CIs). The meta-analysis was performed with fixed-effect model or random-effect model according to the heterogeneity. Six trials including 533 subjects were included. Compared with placebo, ondansetron was associated with a significant reduction of PAS (RR 0.43, 95% CI, 0.27-0.70), without an increased risk of bradycardia (RR 0.37, 95% CI, 0.12-1.15). Compared with meperidine, no difference was observed in the incidence of PAS (RR 0.68, 95% CI, 0.39-1.19) and bradycardia (RR 2.0, 95% CI, 0.38-10.64). Ondansetron has a preventive effect on PAS without a paralleled side effect of bradycardia.